CARP interacts with titin at a unique helical N2A sequence and at the domain Ig81 to form a structured complex - Zhou, Tiankun; Bogomolovas, Julius; Labeit, Siegfried (FEBS letters, 2016)
The cardiac ankyrin repeat protein (CARP) is up-regulated in the myocardium during cardiovascular disease and in response to mechanical or toxic stress. Stress-induced CARP interacts with the N2A spring region of the titin filament to modulate muscle compliance. We characterize the interaction between CARP and titin-N2A and show that the binding site in titin spans the dual domain UN2A-Ig81. We find that the unique sequence UN2A is not structurally disordered, but that it has a stable, elongated α-helical fold that possibly acts as a constant force spring. Our findings portray CARP/titin-N2A as a structured node and help to rationalize the molecular basis of CARP mechanosensing in the sarcomeric I-band.
Gesehen am 21.09.2019
Available online 2 September 2016